Responses of aquatic food webs to the addition of structural complexity and basal resource diversity in degraded Neotropical streams - Ceneviva-Bastos, Mônica [UNESP]; Montaña, Carmen G.; Schalk, Christopher M.; Camargo, Plínio B.; Casatti, Lilian [UNESP] (Wiley, 2017)
The loss of riparian forests can disrupt the structure and function of lotic ecosystems through increased habitat homogenization and decreased resource diversity. We conducted a field experiment and manipulated structural complexity and basal resource diversity to determine their effect on multiple aspects of community and food-web structure of degraded tropical streams. In-stream manipulations included the addition of woody debris (WD) and the addition of wood and leaf packs (WLP). The addition of structural complexity to degraded streams promoted detritus retention and had a positive effect on stream taxonomic richness, abundance and biomass. At the conclusion of the experiment, abundance and richness in the WD-treated reaches increased by over 110% and 80%, respectively, while abundance and richness in the WLP-treated reaches increased by over 280% and 170% respectively. Wood debris and leaves were consumed only by few taxa. Detritivorous taxa were the most abundant trophic guild at the beginning and at the end of the experiment. Food webs in treated reaches were relatively more complex in terms of links and species at the conclusion of the experiment, with highest maximum food chain length in the WD treatments and highest number of trophic species, links, link density, predators and prey at the WLP treatment. Despite differences observed in diet-based food webs, there was little variation in isotopic niche space, likely due to the high degree of omnivory and trophic redundancy, which was attributed to the importance of fine detritus that supported a broad range of consumers. Even in these degraded streams, aquatic taxa responded to the addition of increased complexity suggesting that these efforts may be an effective first step to restoring the structure and function of these food webs.
Keywords: habitat heterogeneity; Neotropics; stable isotope analysis; stream biota; stream restoration